Estudo do efeito dos metabólitos do benzeno e tolueno sobre as mitocôndris cerebrais e hepáticas de ratos - Barreto, George Emílio Sampaio (2005)
Aim: The aim of this work was to investigate the hypothesis that catechol and 3MC inhibit FADH2-linked basal respiration in mitochondria isolated from rat liver and brain homogenates. Moreover, catechol ability to induce DNA damage in rat brain cells through the comet assay (alkaline single-cell gel electrophoresis assay) was also observed. Methods: Two different catechols were evaluated: pirocatechol (derived from benzene) and 3-methylcatechol (derived from toluene); rat liver and brain homogenates were incubated with 1mM catechol at pH 7.4 for up to 30 minutes. After that, mitochondrial fractions were isolated by differential centrifugation. Basal oxygen uptake was measured using a Clark-type electrode after the addition of 10 mM sodium succinate for a period of 12 minutes. In additional experiments, rat brain cells were treated with 1, 5 and 10mM pirocatechol for up to 20 minutes at 37º C, and submitted to electrophoresis. Results: Catechols (pirocatechol and 3methylcatechol) induced a time-dependent partial inhibition of FADH2-linked basal mitochondrial respiration. Indeed, pirocatechol was able to produce a dosedependent DNA oxidative damage in rat brain cells by 2 and 4 injury levels. These results suggest that reactive oxygen species generated by the oxidation of catechols, induced an impairment on mitochondrial respiration and a DNA damage, which might be related to their citotoxicity. Conclusion: Catechols produced an inhibition of basal respiration associated to FADH2 in isolated liver and brain mitochondria; 3-methylcatechol, at the same concentration, produced similar toxicity in the mitochondrial model. Indeed, pirocatechol induced a DNA damage in rat brain cells, mainly observed in comets formation and consequent DNA degradation